ANALISIS KETERAMPILAN MEMBACA INTENSIF SISWA PADA MATA PELAJARAN BAHASA INDONESIA BERDASARKAN MINAT BELAJAR SISWA DI KELAS III SDN 62 SINGKAWANG - Anitra, Rien (Satya Widya, 2022)
This study aims to describe students' intensive reading skills in terms of high, medium and low learning interest in grade III SDN 62 Singkawang. This type of research is qualitative descriptive research. The collection technique uses written test techniques, questionnaires and documentation. Data Analysis is Data Reduction, Data Presentation and Conclusions. The results of this study are 1) Students who have a high interest in learning have skills Sufficient intensive reading, 2) Students who have sufficient interest in learning have sufficient intensive reading skills, 3) Students who have low interest in learning have sufficient intensive reading skills. It can be concluded that students' interest in learning can greatly affect the success in students' intensive reading skills. Intensive reading skills are important for successful learning in Indonesian subjects, and all subjects in school.